Psychological distress as a crucial determinant for quality of life in patients with noncardiac chest pain in Central China: A cross-sectional study. Issue 46 (November 2016) - Zhang, Lei; Tu, Lei; Chen, Jie; Bai, Tao; Song, Jun; Xiang, Xuelian; Wang, Ruiyun; Hou, Xiaohua
Abstract : Abstract: Increased psychiatric comorbidity, predominantly anxiety and depressive symptoms, and lower quality of life (QoL) are associated with noncardiac chest pain (NCCP). We aimed to investigate the roles of anxiety and depression in the impaired QoL of NCCP patients in Central China. In this hospital-based cross-sectional study, 200 consecutive patients who complained of chest pain with normal coronary angiography were enrolled in the Department of Cardiology and Gastroenterology, Union Hospital, Wuhan, China. Meanwhile, 100 healthy controls, with age and sex-matched, were recruited. Upper gastrointestinal endoscopy was undergone and a standardized symptom questionnaire was completed in NCCP patients. Levels of anxiety and depression and QoL were assessed using locally translated and validated versions of the Hospital Anxiety and Depression Scale (HADS) and the 36-item Short Form Health Survey (SF-36), respectively. The NCCP patients had poorer physical and mental QoL compared with the controls, and nearly half of them had anxiety (49.7%) and depression (40.1%). Those with anxiety and/or depression had lower physical (PCS) and mental (MCS) component summary score compared with those without anxiety and depression. Increased levels of anxiety and depression were associated with lower PCS ( r  = −0.469 and −0.523 respectively, P  < 0.001) and MCS ( r  = −0.474 and −0.440, respectively, P  < 0.001). The chest pain, heartburn, and anxiety were independent factors influence on both PCS and MCS. Moreover, psychological distress, besides directly acting on the QoL, may also mediate indirectly effects of physical symptoms on both the physical and mental QoL. We demonstrated that anxiety and depression are important determinants for the QoL of NCCP patients. Therefore, interventions should emphasize on identifying and treating the psychological impact in NCCP.